Computing Ethics Is That Social Bot Behaving Unethically? A procedure for reflection and discourse on the behavior of bots in the context of law, deception, and societal norms. - de Lima Salge, Carolina Alves; Berente, Nicholas (Communications of the ACM, 2017)
The article discusses the relation of social bots to ethical norms and legal culpability in a procedure for social media known as Bot Ethics. Topics include the relation of laws to ethical standards for behavior, the use of deception by bots, and the assignment of responsibility for bot behavior to developers.